Adverse childhood experiences and substance use among Hispanic emerging adults in Southern California. (November 2015) - Allem, Jon-Patrick; Soto, Daniel W.; Baezconde-Garbanati, Lourdes; Unger, Jennifer B.
Abstract: Introduction: Emerging adults who experienced stressful childhoods may engage in substance use as a maladaptive coping strategy. Given the collectivistic values Hispanics encounter growing up, adverse childhood experiences may play a prominent role in substance use decisions as these events violate the assumptions of group oriented cultural paradigms. Alternatively, adverse childhood events might not increase the risk of substance use because strong family ties could mitigate the potential maladaptive behaviors associated with these adverse experiences. This study examined whether adverse childhood experiences were associated with substance use among Hispanic emerging adults. Method: Participants (n = 1420, mean age = 22, 41% male) completed surveys indicating whether they experienced any of 8 specific adverse experiences within their first 18 years of life, and past-month cigarette use, marijuana use, hard drug use, and binge drinking. Logistic regression models examined the associations between adverse childhood experiences and each category of substance use, controlling for age, gender, and depressive symptoms. Results: The number of adverse childhood experiences was significantly associated with each category of substance use. A difference in the number of adverse childhood experiences, from 0 to 8, was associated with a 22% higher probability of cigarette smoking, a 24% higher probability of binge drinking, a 31% higher probability of marijuana use, and a 12% higher probability of hard drug use respectively. Conclusions: These findings should be integrated into prevention/intervention programs in hopes of quelling the duration and severity of substance use behaviors among Hispanic emerging adults. Highlights: Among participants the average number of adverse childhood experiences was two. Verbal abuse was associated with drinking, cigarette, marijuana, and hard drug use. Physical abuse was associated with binge drinking, marijuana, and hard drug use. Parental separation or divorce was associated with cigarette and marijuana use.